So good they can't ignore you why skills trump passion in the quest for work you love - Newport, Cal (Business Plus, 2012)
In they eye-opening account, Cal New port debunks the long-held belief that "follow your passion" is good advice. After making his case against passion, Newport sets out on a quest to discover the reality of how people end up living what they do. Spending time with organic farmers, venture capitalists, screenwriters, freelance computer programmers, and other who admitted to deriving great satisfaction from their work, Newport uncovers the strategies they used and the pitfalls they avoided in developing their compelling careers. Matching your job to a preexisting passion does not matter, he reveals. Passion comes after you put in the hard work to become excellent at something valuable, not before. This will change the way we think about our careers, happiness, and the crafting of a remarkable life